2016
DOI: 10.1088/1009-0630/18/4/04
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cold Plasma on Cell Viability and Collagen Synthesis in Cultured Murine Fibroblasts

Abstract: An argon atmospheric pressure plasma jet was employed to treat L929 murine fibroblasts cultured in vitro. Experimental results showed that, compared with the control cells, the treatment of fibroblasts with 15 s of plasma led to a significant increase of cell viability and collagen synthesis, while the treatment of 25 s plasma resulted in a remarkable decrease. Exploration of related mechanisms suggested that cold plasma could up-regulate CyclinD1 gene expression and down-regulate p27 gene expression at a low … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 30 publications
1
21
0
Order By: Relevance
“…Nitrogen oxides generated from the air plasma dissolve in the liquid forming nitrites and nitrates in the liquid by the reaction ( (aq) means an aqueous species) [24][25][26] It is difficult to detect the concentration of short-lived reactive species in the plasma-treated liquid (PBS) due to the short half-life and high reactivity. However, the presence of the long-lived reactive species in the aqueous phase can provide indirect proof of the existence of short-lived reactive species according to the aforementioned reactions (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13). Figure 3(a) shows the concentrations of hydrogen peroxide, nitrate ion, and ozone in the PBS after the air plasma treatment.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nitrogen oxides generated from the air plasma dissolve in the liquid forming nitrites and nitrates in the liquid by the reaction ( (aq) means an aqueous species) [24][25][26] It is difficult to detect the concentration of short-lived reactive species in the plasma-treated liquid (PBS) due to the short half-life and high reactivity. However, the presence of the long-lived reactive species in the aqueous phase can provide indirect proof of the existence of short-lived reactive species according to the aforementioned reactions (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13). Figure 3(a) shows the concentrations of hydrogen peroxide, nitrate ion, and ozone in the PBS after the air plasma treatment.…”
Section: Resultsmentioning
confidence: 99%
“…Suggested as a promising approach to diseases including cancer, various types of CAPs based on different power sources and configurations have been developed because they interact with tissue or cell without a significant temperature increase [1][2][3][4][5]. In particular, the atmospheric-pressure plasma jet is often used to treat cells in vitro and in vivo [6][7][8][9][10]. It has also been demonstrated that CAPs can induce cell apoptosis or necrosis.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the various cell types, the TME consists of collagen, elastin, fibronectin, glycoproteins, and proteoglycan [92]. It has been observed that prolonged treatment with CAP inhibits cell viability and collagen production of murine fibroblasts [93]. A reduction in collagen secretion and the migration behavior was also observed after CAP treatment in keloid fibroblasts, which, like tumor-associated fibroblasts, show an overproduction of collagen [94,95].…”
Section: Cap Interaction With the Tumor Microenvironmentmentioning
confidence: 99%
“…CAFs are considered critical players in the malignant progression with a complex bidirectional communication mechanism between CAFs and cancer cells mediated by cytokines and RNA transference via exosomes to favour metastasis, vascular permeability, and resistance to chemotherapy and radiotherapy [111][112][113]. It has been proposed that plasma has dual effects on fibroblasts, as short treatments enhanced the cell viability and collagen production, whereas longer treatments inhibit them [114]. Exposure to longer plasma treatments of higher plasma-derived ROS concentrations can induce senescence [115] and necrotic cell death in fibroblasts [116].…”
Section: Cellular Components Of the Tumour Microenvironmentmentioning
confidence: 99%